Perceived naturalness of facial expression after hyaluronic acid filler injection in nasolabial folds and lower face. (6th November 2019) - Philipp‐Dormston, Wolfgang G.; Schuster, Bernd; Podda, Maurizio
Abstract: Background: In addition to having a younger and more attractive appearance after facial aesthetic treatment, patients desire natural‐looking and long‐lasting results. Objective: To evaluate perceived naturalness of dynamic facial expressions after treatment with hyaluronic acid fillers in nasolabial folds (NLFs) and lower face wrinkles and folds. Methods: Subjects requiring treatment of moderate‐to‐severe NLFs and at least one other lower face indication were treated with hyaluronic acid fillers. Assessments included perceived naturalness, attractiveness and age, NLF severity, aesthetic improvement, satisfaction, and safety. Results: Sixty‐three subjects were enrolled. Six months after treatment, naturalness of facial expression was maintained or enhanced for ≥98% of subjects, attractiveness was enhanced for ≥61% of subjects, and ≥34% of subjects looked younger, as assessed by investigators and an independent evaluator. Wrinkle severity had improved at least 1 grade for ≥54% of subjects at Month 12. Aesthetic improvement was reported for ≥92% of subjects 12 months after treatment. Satisfaction with treatment outcome was high. Local tolerability events and adverse events were mainly mild or moderate and resolved spontaneously. Conclusion: Hyaluronic acid treatment in NLFs and lower face was well tolerated and achieved natural‐looking results, long‐lasting aesthetic improvement, and high satisfaction with treatment outcome.